Digital Management Accounting as a Tool for Strategic Decision-Making by MSME Owners: A Systematic Literature Review - Mediaty; Asri Usman; Andi Naimah Syakir; Mulia Suardi (PT. Anagata Sembagi Education, 2026)
Micro, small, and medium enterprises (MSMEs) constitute the backbone of many emerging economies, yet a large share of their owners continue to rely on intuition rather than structured financial information when making strategic decisions. Digital management accounting (DMA) the integration of cloud-based bookkeeping, accounting information systems, big data analytics, and artificial intelligence into management accounting practice has been proposed as a mechanism to close this gap. This study conducts a systematic literature review (SLR) following the PRISMA protocol to examine how digital management accounting supports strategic decision-making among MSME owners. Twenty-five peer-reviewed articles published between 2021 and 2026, drawn from Scopus, Google Scholar, DOAJ, and Consensus, were analyzed thematically. The review finds that DMA improves decision quality through three interrelated mechanisms: (1) enhanced information quality and timeliness, (2) cost and resource efficiency, and (3) expanded analytical capacity through big data and artificial intelligence. However, adoption remains constrained by digital literacy gaps, infrastructure limitations, and resource-based barriers specific to MSMEs. The novelty of this review lies in synthesizing fragmented, largely single-country evidence into an integrated conceptual model linking digital management accounting adoption, information quality, and strategic decision outcomes, while identifying under-researched areas such as artificial intelligence-based management accounting for micro-scale enterprises in developing economies.